2011
DOI: 10.1038/nature10535
|View full text |Cite
|
Sign up to set email alerts
|

Structure and reactivity of a mononuclear non-haem iron(III)–peroxo complex

Abstract: Oxygen-containing mononuclear iron species—iron(III)–peroxo, iron(III)–hydroperoxo and iron(IV)–oxo—are key intermediates in the catalytic activation of dioxygen by iron-containing metalloenzymes1–7. It has been difficult to generate synthetic analogues of these three active iron–oxygen species in identical host complexes, which is necessary to elucidate changes to the structure of the iron centre during catalysis and the factors that control their chemical reactivities with substrates. Here we report the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
333
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(358 citation statements)
references
References 31 publications
23
333
2
Order By: Relevance
“…The missing link connecting the mechanistic steps of the above studies was the experimental demonstration of O-O bond cleavage in a hydroperoxoiron(III) complex to yield the corresponding high-valent iron-oxo species. This link has recently been identified independently by the groups of Li et al 56 and Cho et al, who generated a high-spin Fe III -OOH complex supported by the Me 4 cy ligand via protonation of the side-on peroxoiron(III) conjugate base 56,57 . This hydroperoxo complex was shown to convert quantitatively to the corresponding S = 1 oxoiron(IV) complex either through acid-mediated O-O bond heterolysis, followed by the reduction of the transient oxoiron(V) intermediate 56 46, also reacts with O 2 to yield an oxoiron(III) intermediate, which is proposed to derive from the reduction of an initially formed oxoiron(IV) species.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…The missing link connecting the mechanistic steps of the above studies was the experimental demonstration of O-O bond cleavage in a hydroperoxoiron(III) complex to yield the corresponding high-valent iron-oxo species. This link has recently been identified independently by the groups of Li et al 56 and Cho et al, who generated a high-spin Fe III -OOH complex supported by the Me 4 cy ligand via protonation of the side-on peroxoiron(III) conjugate base 56,57 . This hydroperoxo complex was shown to convert quantitatively to the corresponding S = 1 oxoiron(IV) complex either through acid-mediated O-O bond heterolysis, followed by the reduction of the transient oxoiron(V) intermediate 56 46, also reacts with O 2 to yield an oxoiron(III) intermediate, which is proposed to derive from the reduction of an initially formed oxoiron(IV) species.…”
mentioning
confidence: 75%
“…Labelling experiments with 57 Fe as well as 15 However, in a subsequent in-depth spectroscopic and theoretical work, Aliaga-Alcalde et al 82 concluded that [(cy-ac)Fe V (N)] + has an unusual orbitally degenerate S = 1/2 ground state. Initially, the Fe-N stretch in [(cy-ac)Fe V (N)] + could not be identified in the infrared vibrational spectrum.…”
Section: Iron-nitrido Model Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Under alkaline conditions, the iron(III)-peroxo species, acknowledged as nucleophilic oxidant intermediates, are subjected to production by the reaction of H2O2 with iron porphyrins and non-heme iron complexes (Cho et al 2011;Franke et al 2012). Thus, it is reasonable to assume that the metalloporphyrins in glucose oxidation might be responsible for the formation of the metalo-peroxo species, (TSPPMO2 -), by the addition of H2O2 generated in situ.…”
Section: Resultsmentioning
confidence: 99%
“…They are widely used in stoichiometric as well as catalytic oxidation in organic and biochemistry [3], for example in the oxidation of thioanisole [4], methyl benzenes [5], tertiary amines, alkenes, alcohols [6], bromide [7] and also in olefin epoxodations [8]. Peroxo complexes of uranium are attracting interest as oxidants in organic synthesis [9].…”
Section: Introductionmentioning
confidence: 99%